2020
DOI: 10.1111/apt.15765
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: management of localised low‐grade upper gastrointestinal neuroendocrine tumours

Abstract: Background: Neuroendocrine tumours (NETs) of the stomach and duodenum are rare, but are increasing in incidence. Optimal management of localised, low-grade gastric and duodenal NETs remains controversial. Aims:To systematically review recent literature that has evaluated the management of localised low-grade gastric and duodenal NETs. Methods:A systematic literature search was conducted. Articles were screened and eligible articles fully assessed. Additional articles were identified through the included articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 72 publications
1
27
0
Order By: Relevance
“…Patient management plans, therefore, need to be personalized and take all these features into account. The current ENETS management guidelines recommend resection of all d-NETs, with the mode of resection being influenced largely by the size of the tumour [8, 15, 16]. A recent study by Gamboa et al [17] supported this argument as the authors demonstrated improved overall survival with any type of resection regardless of tumour size when compared to no resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient management plans, therefore, need to be personalized and take all these features into account. The current ENETS management guidelines recommend resection of all d-NETs, with the mode of resection being influenced largely by the size of the tumour [8, 15, 16]. A recent study by Gamboa et al [17] supported this argument as the authors demonstrated improved overall survival with any type of resection regardless of tumour size when compared to no resection.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent ENETS treatment guidelines advocate resection for all d-NETs using either endoscopic or surgical techniques [7]. We recently published a systematic review of the management of localized low-grade upper gastrointestinal NETs and found that a few studies had also reported favourable outcomes for patients who had not undergone resection of small, low-grade, non-functioning, non-ampullary d-NETs [8]. Despite limited follow-up data, Burke et al [9] reported 12 patients who did not undergo any treatment with 11 patients being alive after 11 months of mean follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…The duodenum is thin walled and has a narrow lumen making endoscopic resection more challenging and associated with significant risk of perforation and bleeding [18]. ESD is associated with far greater risk than in the lower GI tact and perforation has been reported in up to 30% of cases in the duodenum [12].…”
Section: Discussionmentioning
confidence: 99%
“…The current ENETS dNENs management guidelines recommend endoscopic removal of all non-functioning dNENs <1cm [1]. The incidence of complications post endoscopic resection has recently been reported as 8.6% (24/279) in a systematic review of 21 retrospective studies [12].The proportion of resections with tumour present at the margin (R1) has been reported as high as 40% [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to the consensus guidelines of the European Neuroendocrine Tumour Society (ENETS) treatment of D-NETs is mainly guided by tumour size, i.e., tumours <1 cm should be treated endoscopically, tumours >2 cm should be considered for surgical resection whereas treatment of tumours 1-2 cm is not standardized [10]. A recent systematic review identified only few studies reporting outcomes and recurrence rates after treatment of D-NETs and the evidence supporting the current treatment recommendations is limited [17,18]. We therefore aimed to assess the overall survival and recurrence rate in a cohort of patients with D-NETs.…”
Section: Introductionmentioning
confidence: 99%